Stalactitization of concrete structures, thin coating formation and its reduction/Betoninių konstrukcijų stalaktitizacija, apnašų susidarymas ir jų mažinimas - Kazragis, Loreta; Valaitytė, Halina (Journal of Civil Engineering and Management, 1999)
Concrete and reinforced concrete construction of buildings and bridges, concrete slabs for laying streets, concrete tiles for laying pavements and squares are often covered with thin coating reminding of stalactites or white-grey flows. This phenomenon can be called stalactitization of concrete. It does not just worsen the decorative properties of concrete and reinforced concrete, but also weakens the mechanical strength of these materials. We discuss the reasons of stalactitization of concrete and reinforced concrete constructions and articles and recommend means to weaken this process. The processes of concrete structure stalactitization and formation of thin coating can be delayed in the following ways: 1. Using a filler in production, which has calcite and limestone as little as possible, and controlling their amount by methods of chemical analysis. 2. For CaO (0,5%), present in Portland cement, and for forming Ca(OH)2 in concrete neutralization substances containing SiO2 and SiO2 nH2O can be used but, to prevent alkaline corrosion of concrete, they can be applied only when Portland cement contains very little Na2O and K2O. 3. If there is a possibility, do not use passivated Portland cement containing FeSO4 and A1(SO4)3. 4. Avoid an excess of water when making concrete mixtures. 5. Coloured or other concrete articles should be stored under a roof or at least be covered. Article in Lithuanian. First Published Online: 26 Jul 2012